Hubungan antara Kemampuan Literasi Digital, Keterlibatan Orang Tua, Kemampuan Komunikasi dengan Hasil Belajar Pendidikan Agama Kristen Kelas VIII SMP di SDH Daan Mogot - Billy Jonathan; Pujianto Yugopuspito (Journal on Education, 2024)
Christian Education plays a crucial role in shaping the character and fostering an understanding of Christian values in students' lives. However, the proliferation of digital information and the lack of parental attention pose challenges to students' development. This research aims to investigate the relationship between digital literacy skills, parental involvement, communication skills, and the learning outcomes of Christian Education among eighth-grade students in junior high schools. A quantitative correlational research method was employed, and a total of 188 students were sampled. The data was collected through questionnaires as well as formative and summative assessment data of learning outcomes in Christian Religious Education. The research findings indicate a significant relationship between digital literacy skills and the learning outcomes of Christian Education. Furthermore, a significant relationship was observed between communication skills and the learning outcomes of Christian Education. However, no significant relationship was found between parental involvement and the learning outcomes of Christian Education. In conclusion, enhancing students' digital literacy skills and communication skills are crucial factors in improving the learning outcomes of Christian Education. Recommendations for future research include employing different methodologies to explore students' experiences that support learning outcomes.